2010
DOI: 10.1088/0004-637x/725/2/1452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cluster Physics on the Sunyaev-Zel'dovich Power Spectrum

Abstract: We use an analytic model to investigate the theoretical uncertainty on the thermal Sunyaev-Zel'dovich (SZ) power spectrum due to astrophysical uncertainties in the thermal structure of the intracluster medium. Our model accounts for star formation and energy feedback (from supernovae and active galactic nuclei) as well as radially dependent non-thermal pressure support due to random gas motions, the latter calibrated by recent hydrodynamical simulations. We compare the model against X-ray observations of low-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
394
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(422 citation statements)
references
References 75 publications
(169 reference statements)
25
394
3
Order By: Relevance
“…Since the "actual" total mass is also partially supported by non-thermal pressure, we model the non-thermal pressure fraction using the form given in Shaw et al (2010),…”
Section: Cluster Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the "actual" total mass is also partially supported by non-thermal pressure, we model the non-thermal pressure fraction using the form given in Shaw et al (2010),…”
Section: Cluster Modelingmentioning
confidence: 99%
“…where Ptot is total gas pressure, f (r, z) = a(z) r r 500 nnt , a(z) = a0(1 + z) β with a0 = 0.18 ± 0.06, β = 0.5 and nnt = 0.8 ± 0.25 (Shaw et al 2010). We also study the effect of different non-thermal pressure fraction by varying a0.…”
Section: Cluster Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…One advantage of using the tSZ angular power spectrum over cluster counts is that no explicit measurement of cluster masses is required. Also, lower mass, and therefore fainter, clusters, which may not be detected as individual objects, contribute to this statistical signal (Battaglia et al 2010;Shaw et al 2010). However, significant drawbacks of using the tSZ angular power spectrum include potential contamination from point sources (Rubiño-Martín & Sunyaev 2003;Taburet et al 2010) and other foregrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scales probed are particularly sensitive to the uncertainties in modelling the intracluster medium (ICM) over a broad range of masses and redshifts, and at large clustercentric radii (Battaglia et al 2010). Recent work, using hydrodynamical simulations (Battaglia et al 2010(Battaglia et al , 2012) N-body simulations plus semi-analytic gas models (Trac et al 2011) and purely analytic models (Shaw et al 2010), have significantly reduced the tension between the observed and predicted values. However the distribution of amplitudes between different mod- els and simulations is still significantly larger than the measurement errors, degrading the constraints that can be placed on cosmological parameters with these methods (Dunkley et al 2013;Reichardt et al 2013).…”
Section: Introductionmentioning
confidence: 99%